TEACHING STRATEGIES FOR EFL INCLUSIVE EDUCATION: A STUDY OF HEARING-IMPAIRED STUDENTS - Baiq Qori'atul Hafizah; Roro Millatu Al Ghaniy (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
Teaching English as a Foreign Language Learning (EFL) to hearing-impaired students encountered several challenges due to teachers’ lack of readiness. Previous studies reported that it was caused by insufficient training, leading to inadequate knowledge and skills. Therefore, this study aims to explore challenges encountered by teachers in EFL in an inclusive education setting, the strategies they used to address these challenges, and students’ responses to the strategies implemented. This study employed a qualitative design involving two participants from two different private secondary schools. Data were collected through semi-structured interviews and were analyzed using verbatim transcripts and repeated reading to achieve familiarity. The researcher then selected and marked relevant data and manually coded them into the main themes. The result shows that teachers encountered challenges related to communication barriers, students' struggles with understanding new vocabulary, parental support, teacher training, and the use of hearing aids. To overcome these challenges, teachers implemented several strategies, such as participating in training, Universal Design for Learning (UDL), Differentiated Instruction, Program Pembelajaran Individu (PPI), multimodal learning, and duality. In addition, students responded the strategies positively, as they increase in learning engagement, classroom participation, and learning outcomes. A key finding of this study is that dual-language practices or bilingualism functions not only as communication medium but also as a pedagogical approach that enhance students cognitive abilities. Through this study, teachers can adapt strategies to address various challenges in EFL learning with hearing-impaired students and school administrators can implement policies, such as supporting teachers with training in implementing inclusive education.